Determination of circular membrane parameters from its resonance frequencies - ZIÓŁKO, Mariusz (Archives of Acoustics, 1988)
Circumferential forces, speed of elastic wave and dissipation of energy factor are calculated from resonance frequencies of circular membranes made of tantalum and nickel-chromium steel. The results obtained for a mathematical model without dissipation are compared with the results obtained for a model with dissipation of energy. The assignment of the coefficient of partial differential equation is presented for this second case. An algorithm applied to computer simulation of membrane vibrations is based on the "leap frog" difference method.